(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2018)
In this paper, the combine effect of two industrial wastes fly ash and stone dust on Atterberg’s limit, compaction characteristic, unconfined compressive strength (UCS), California bearing ratio (CBR) of clayey soil have been discussed. To maintain Sustainable environment, there is need to utilize industrial wastes for improving geotechnical properties of soil. Therefore in this paper an attempt is made to stabilize expansive clayey soil by using two low cast materials fly ash and stone dust fly ash possesses only pozzolanic properties and no coarser soil particles whereas stone dust is a material that possesses pozzolanic as well as coarser contents in it.